2019
DOI: 10.1038/s41467-019-11696-7
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic stress-triggered β-catenin/JDP2/PRMT5 complex facilitates reestablishing glutathione homeostasis

Abstract: The mechanisms underlying how cells subjected to genotoxic stress reestablish reduction-oxidation (redox) homeostasis to scavenge genotoxic stress-induced reactive oxygen species (ROS), which maintains the physiological function of cellular processes and cell survival, remain unclear. Herein, we report that, via a TCF-independent mechanism, genotoxic stress induces the enrichment of β-catenin in chromatin, where it forms a complex with ATM phosphorylated-JDP2 and PRMT5. This elicits histone H3R2me1/H3R2me2s-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…Alterations in the ratio of the redox pair 2GSH/GSSG towards a more oxidized status form the biochemical basis of targeting redox-sensitive cysteine residues in proteins. As an antioxidant, GSH removes ROS directly or indirectly and limits the lifetime of the oxidative signal [33]. GSH is also a substrate of several antioxidant enzymes.…”
Section: Ros and Antioxidant Pathwaysmentioning
confidence: 99%
“…Alterations in the ratio of the redox pair 2GSH/GSSG towards a more oxidized status form the biochemical basis of targeting redox-sensitive cysteine residues in proteins. As an antioxidant, GSH removes ROS directly or indirectly and limits the lifetime of the oxidative signal [33]. GSH is also a substrate of several antioxidant enzymes.…”
Section: Ros and Antioxidant Pathwaysmentioning
confidence: 99%
“…Histone methylation is found among basic amino acid lysine, arginine and histidine [121]. Numerous studies have demonstrated the significant role of histone methylation in breast cancer progression and metastasis [122,123]. [112,114] 5.…”
Section: Histone Modifications and Their Role Is Breast Cancer Metastmentioning
confidence: 99%
“…Genotoxic stress, including chemotherapy, induces interaction between β-catenin, ATM-phosphorylated JDP2 (Jun dimerization protein 2) and PRMT5, resulting in transcription of genes implicated in redox homeostasis. In this process, H3R2me1/H3R2me2s catalyzed by PRMT5 recruits the WDR5/MLL complex resulting in H3K4me3 and transcriptional activation of redox-related genes [39]. PRMT5 forms a complex with the adaptor protein SHARPIN implicated in H3R2me1 modification and recruitment of WDR5-ASH2 (MLL-component), facilitating formation of H3K4me3 on genes functioning in metastasis [40].…”
Section: Prmt5 Control Of Gene Expression By Histone Methylationmentioning
confidence: 99%